Evidence of Submicroscopic Malaria Parasitemia, Soil-Transmitted Helminths, and Their Coinfections Among Forest-Fringed Orang Asli Communities in Peninsular Malaysia - Nurmanisha, Abdull Majid; Yap, Nan Jiun; Tee, Mian Zi; Er, Yi Xian; Romano, Ngui; Yvonne Lim, Ai Lian (the American Journal of Tropical Medicine and Hygiene, 2025)
Malaysia’s malaria rate has declined but remains a public health concern, with limited investigations into malaria and coinfections with soil-transmitted helminth (STH) infections. A cross-sectional study using convenience sampling in Orang Asli villages enrolled 437 villagers aged 1–83 years based on their willingness to participate. Blood samples were tested microscopically for malaria, followed by nested polymerase chain reaction (PCR), and stool samples were screened microscopically for STH eggs. Body temperature, demographic, and socioeconomic data were collected. Malaria parasite was detectable only via PCR, with a 15.3% prevalence, indicating submicroscopic malaria parasitemia; none of the positive cases presented fever. The identified species included Plasmodium vivax (8.7%), Plasmodium cynomolgi (5.5%), Plasmodium knowlesi (4.3%), Plasmodium falciparum (1.8%), Plasmodium inui (0.2%), and Plasmodium malariae (0.2%). Females had significantly higher rates of submicroscopic malaria parasitemia (19.6%) compared with males (9.3%, P = 0.003). STH infections were highly prevalent (71.4%), with Trichuris trichiura (65.2%), Ascaris lumbricoides (35.0%), and hookworm (14.6%). STH infection was associated with age (P <0.001), peaking in individuals aged 10–19 years (86.2%) and 1–9 years (83.0%), as well as with students (84.3% versus 60.8% in employed and 60.3% in unemployed; P <0.001) and low-income households (76.4% versus 61.7% in higher-income households; P = 0.002). Submicroscopic malaria parasitemia and STH coinfections were present in 8.9% of participants, with higher rates in low-income households (12.6% versus 5.2% in higher-income, P = 0.010). The Negrito tribe exhibited the highest prevalence of submicroscopic malaria parasitemia, STH, and coinfections (P <0.05). This study highlights the need for integrated malaria and STH control strategies, particularly for the Negrito tribe.